GAMBARAN ELEKTROENSEFALOGRAFI PADA MENINGITIS TUBERKULOSIS YANG MENGALAMI BANGKITAN SIMTOMATIK AKUT - Suryani Gunadharma,* Sobaryati,* Hendra Irawan* (NEURONA, 2020)
INTRODUCTIONS ELECTROENCEPHALOGRAPHY EEG CAN DETECT ABNORMAL CORTICAL EXCITABILITY CAUSING EPILEPTIC SEIZURE ACUTE SYMPTOMATIC SEIZURE CAN CAUSED BY TUBERCULOUS MENINGITIS TBM WHICH CAN FURTHER DEVELOPE TO SYMPTOMATIC EPILEPSY WE ARE INTERESTED TO STUDY THE CHARACTERISTIC OF EEG PATTERN IN TBM PATIENTS WITH ACUTE SYMPTOMATIC SEIZURE